The Effect of Calorie Tracking on Eating Behaviors of University Students - Bülent Keskin; Esra Özay Köse (Universitas Pendidikan Indonesia, 2023)
This paper aims to determine whether tracking calories using a mobile application without any nutrition education has a positive effect on the eating behaviors of university students. The concurrent design, one of the mixed methods designs, was used to compare the quantitative and qualitative data analysis results. The participants are 108 university students who voluntarily agreed to participate in the study. In the quantitative part of the study, a calorie tracking form was used; in the qualitative part, an interview form was used to determine eating behaviors. The students were not given any information about healthy nutrition and were only asked to track calories. The change in body mass index values obtained from the calorie tracking form is presented with the Wilcoxon signed ranks test. In evaluating the data obtained from the interview form determining eating behaviors, the data were categorized by content analysis, and the categories were presented as percentage values. According to the data obtained, it has been observed that positive behavioral changes in terms of nutrition can be created even without giving any information about healthy nutrition to the students, just by making them track calories. As a result of the activity, they became aware of which foods would make them gain weight and which would not and gained positive eating behaviors. Based on the results obtained from this study, recommendations for future studies and public health were made.